A constitutive material model for a commercial PMMA bone cement using a combination of nano-indentation test and finite element analysis. (May 2017) - Shirazi, H. Asgharzadeh; Mirmohammadi, S.A.; Shaali, M.; Asnafi, A.; Ayatollahi, M.R.
Abstract: To obtain accurate mechanical properties of an orthopedic Polymethylmethacrylate (PMMA-based) bone cement, nanomechanical testing was performed. Due to visoelastic characteristics of this polymer-like bone cement, the mechanical properties cannot be identified using conventional indentation methods. A well-known two-layer viscoplasticity model was selected and simulated in a finite element solver. A complete analogical study between the results of the finite element simulation and the experimental data was made to reach the best optimized parameters for the selected model. It is shown that the proposed model can be used to obtain the constitutive material relationship for polymeric materials.